Chapter 36 'Digitising The Mental Health Act' Are we facing the app-ification and platformisation of coercion in mental health services? - Gooding, Piers (Taylor & Francis, 2024)
Socio-technical systems such as video conferencing, digital care work platforms, and electronic health records are taking an increasing role in mental health-related law, particularly since the COVID-19 pandemic. Reflecting on these experiments can help navigate an increasingly digital future for mental health services and the laws that govern them. This chapter looks to England and Wales, where an explicit policy aim to 'digitise the Mental Health Act' has seen three key developments: (1) remote medical assessments of persons facing involuntary intervention, (2) the remote operation of tribunals that authorise involuntary interventions, and (3) and the rise of digital platforms for Mental Health Act assessment setup. The chapter argues that although courts appear responsive to the issues posed by the first two developments, there appear to be less obvious oversight of digital platforms used to setup mental health crisis work. The chapter considers legal issues raised by 'digitising mental health legislation' and draws in a political economy perspective to reflect on the role of the private sector in emerging configurations of digitised health and social services. It recommends attention to safeguards in both the procurement and commissioning of private sector practices concerning mental health crisis work and in the proliferation of digital platforms in health and social care services.